Optimisation Of Reinforcement Design Of Coal Mine Roadways (ef04df4d-16ce-4e1d-9fd1-73fd46706558) - Winton J. Gale (International Conference on Ground Control in Mining, 1992)
The design of the reinforcement systems required to stabilise mine roadways has developed through the application of field measurement techniques. These techniques have allowed the level of security of a given opening to be determined from an assessment of the loading within the reinforcement, the extent of roof deformation and experience. The design systems developed are now used extensively in a wide variety of geological environment. Recent interpretative techniques have been developed to improve the level of confidence when designing roadway reinforcement. The techniques are particularly applicable for roadways subject to either weak materials or extreme stress levels. A second area of application is where roadway advance rates and hence the timing of reinforcement placement are critical. The newly developed techniques include both analytical and computational models. The validated computational techniques allow a more rational approach to investigation of the effect of varying reinforcement type, timing of placement and density on the level of stability achieved.